Changes in the intellectual structure of strategic management research: a bibliometric study of the Strategic Management Journal , 1980–2000 - Ramos‐Rodríguez, Antonio‐Rafael; Ruíz‐Navarro, José (Strategic Management Journal, 2004)
Abstract The aim of this paper is to identify the works that have had the greatest impact on strategic management research and to analyze the changes that have taken place in the intellectual structure of this discipline. The methodology is based on the bibliometric techniques of citation and co‐citation analysis which are applied to all the articles published in the Strategic Management Journal from its first issue in 1980 through 2000. Copyright © 2004 John Wiley & Sons, Ltd.